Green Entrepreneurship Sebagai Pilar Pendidikan Kejuruan: Inovasi untuk Kemandirian Ekonomi dan Kelestarian Lingkungan - Ratna Fajarwati Meditama (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
Vocational education has a strategic role in forming human resources who are ready to face work challenges. In this era, the concept of green entrepreneurship is important to be integrated into the vocational education curriculum. This study aims to instill environmental awareness and sustainable business ethics in vocational education. Through this innovation, students are encouraged to develop environmentally friendly business ideas that are oriented towards economic independence. Case studies and project-based learning approaches are used to explore how this concept can be effectively applied in a vocational education environment. The results of the study indicate that the integration of green entrepreneurship in vocational education not only improves students' competence in the field of entrepreneurship, but also encourages the creation of businesses that contribute to environmental sustainability. Vocational education plays an important role in preparing a generation of entrepreneurs who are ready to face economic and ecological challenges in the future.